Exosomal biomarkers of brain insulin resistance associated with regional atrophy in Alzheimer's disease - Mullins, Roger J.; Mustapic, Maja; Goetzl, Edward J.; Kapogiannis, Dimitrios (Human brain mapping, 2017)
Brain insulin resistance (IR), which depends on insulin‐receptor‐substrate‐1 (IRS‐1) phosphorylation, is characteristic of Alzheimer's disease (AD). Previously, we demonstrated higher pSer312‐IRS‐1 (ineffective insulin signaling) and lower p‐panTyr‐IRS‐1 (effective insulin signaling) in neural origin‐enriched plasma exosomes of AD patients vs. controls. Here, we hypothesized that these exosomal biomarkers associate with brain atrophy in AD. We studied 24 subjects with biomarker‐supported probable AD (low CSF Aβ42). Exosomes were isolated from plasma, enriched for neural origin using immunoprecipitation for L1CAM, and measured for pSer312‐ and p‐panTyr‐IRS‐1 phosphotypes. MPRAGE images were segmented by brain tissue type and voxel‐based morphometry (VBM) analysis for gray matter against pSer312‐ and p‐panTyr‐IRS‐1 was conducted. Given the regionally variable brain expression of IRS‐1, we used the Allen Brain Atlas to make spatial comparisons between VBM results and IRS‐1 expression. Brain volume was positively associated with P‐panTyr‐IRS‐1 and negatively associated with pSer312‐IRS‐1 in a strikingly similar regional pattern (bilateral parietal‐occipital junction, R middle temporal gyrus). This volumetric association pattern was spatially correlated with Allen Human Brain atlas normal brain IRS‐1 expression. Exosomal biomarkers of brain IR are thus associated with atrophy in AD as could be expected by their pathophysiological roles and do so in a pattern that reflects regional IRS‐1 expression. Furthermore, neural‐origin plasma exosomes may recover molecular signals from specific brain regions. Hum Brain Mapp 38:1933–1940, 2017. © 2017 Wiley Periodicals, Inc.